A case report on trans-fibular approach to distal tibial giant cell tumor - Y V S Prabhakar; N Srinivasan (MRIMS Journal of Health Sciences, 2016)
Surgical excision of tumors of distal tibia situated specially in poster lateral aspect may be difficult to visualize in its entirety by antero-lateral approach. If posterior approach is chosen, the difficulty in positioning of the patient and important structures behind may cause hesitation in surgeons mind. The trans-fibular approach in selected cases may be indicated for full visualization of the tumor boundary in its entirety. We report one case of osteoclastoma of distal tibia in which osteotomy and subsequent replacement of distal fibula and fixation with a semitubular plate, allowed complete excision of tumor and satisfactory outcome. This procedure provides an alternative technique to the anterior approach.